(untitled) (Global Journal of Medical Research, 2022)
The infectious spread of corona-virus disease (COVID-19) has been prevailing in more than two hundred countries and causing millions of deaths worldwide. The pandemic has wreaked havoc in all sectors of life. Since COVID-19, the most common and effective preventive measure to control the transmission has been to wear face masks. With the decline of infectious virus cases in most countries due to vehement vaccination programs, people are now reluctant to wear masks. However, the recent variants of the virus, such as Delta, Omicron, etc., have proven to be resistant to a degree against vaccines. So, there is no alternative to wearing masks to protect ourselves and those around us. The proposed work in this paper implements a fullproof automated system to detect whether a person has worn a mask and warns the person if he has not.